High viral infection rates in Antarctic and Arctic bacterioplankton - Sawstrom, C; Graneli, W; Laybourn-Parry, J; Anesio, AM (Environmental Microbiology, 2007)
The frequency of visibly phage-infected bacterialcells (FVIB) and the average number of phagesper cell [i.e. burst size (BS)] were determined inAntarctic and Arctic ultra-oligotrophic freshwaterenvironments. Water samples were collected fromtwo Antarctic freshwater lakes and cryoconite holesfrom a glacier in the Arctic. Data from this bipolarstudy show the highest FVIB (average 26.1%, range5.1% to 66.7%) and the lowest BS (average 4, range215) ever reported in the literature. The bacterialdensity is low in these ultra-oligotrophic freshwaterenvironments but a large proportion of the bacteriaare visibly infected. Our results suggest that a constantvirioplankton population can be maintained inthese extreme environments even though hostdensity is low and often slow growing.